Comprehensive Risk Assessment of LAD Disease Progression in CCTA: The CLAP Score Study - Antonella Tommasino; Federico Dell’Aquila; Marco Redivo; Luca Pittorino; Giulia Mattaroccia; Federica Tempestini; Stefano Santucci; Matteo Casenghi; Francesca Giovannelli; Stefano Rigattieri; Andrea Berni; Emanuele Barbato (Journal of Cardiovascular Development and Disease)
Background: a wider left main bifurcation angle (LMBA) has been linked to severe plaque development in the proximal left anterior descending artery (LAD). This study aimed to identify predictors of severe proximal LAD stenosis and major adverse cardiovascular events (MACE) using coronary computed tomography angiography (CCTA). Methods: from an initial cohort of 650 consecutive patients, we analyzed 499 patients who met the inclusion criteria after exclusions. Plaque morphology and characteristics were assessed by CCTA, and MACE occurrences were recorded at follow-up. A predictive score for LAD disease progression (CLAP score) was developed and validated. Results: severe proximal LAD stenosis was detected in 32% (160/499) of patients by CCTA. MACE occurred in 12.5% of patients at follow-up. Significant predictors of MACE were LMBA > 80° (HR: 4.47; 95% CI: 3.80–6.70; p < 0.001), diabetes (HR: 2.94; 95% CI: 1.54–4.63; p = 0.031), chronic kidney disease (HR: 1.71; 95% CI: 1.31–6.72; p = 0.041), high-risk plaques (HR: 2.30; 95% CI: 1.45–3.64; p < 0.01), obstructive CAD (HR: 2.50; 95% CI: 1.50 to 4.10, p = 0.01), and calcium score (CAC) (HR: 1.05; 95% CI: 1.02–1.08, p = 0.004). The CLAP score demonstrated good discriminatory power in both the development (AUC 0.91; 95% CI: 0.86–0.96) and validation cohorts (AUC 0.85; 95% CI: 0.79–0.91); Conclusions: LMBA > 80°, diabetes, chronic kidney disease, obstructive CAD, CAC score >180 and high-risk plaques were significant predictors of MACE in CCTA patients. The CLAP score effectively predicted LAD disease progression, aiding in risk stratification and optimization of intervention strategies for suspected coronary artery disease.